Enhancement of the Capability of Educators through Capacity Building Process - Sripirabaa, B.; Maheswari, T. Sudha (Gyan Management Journal, 2012)
The current globalised scenario has created lots of challenges for the Indian education system. Educational institutions focus in designing curriculum in par with the industry requirements, devising and implementing new pedagogical tools for enhancing the effectiveness and efficiency of the teaching learning process, augmenting the capability of educators through a plethora of development programs, increasing the employability of students and effective utilization of their resources to compete in the current globalized educational scenario. This necessitates assessment of the capability of educators so as to achieve excellence in imparting the desired knowledge, skills and abilities to the students.The objective of the present study is to extend the concept of Capacity Building Process to assess the capability of educators using a developed and validated instrument SSE CAT. The variables for the study were derived from literature reviews. The study subjects were 310 educators selected from management, arts and science and engineering extremes from 18 institutions in Coimbatore district. Capacity mapping was done by plotting the scaled scores on the GRID to identify the lack areas and strategies were devised to enhance the capability of educators. The research described here provides a new methodology for assessing and consequently enhancing the capability of educators through a perception-based, consensus-oriented assessment.